Introductory Remarks on the Stratification of Borrowings through the Work of Mary Serjeantson - Mikulas, Dalibor (Communications - Scientific letters of the University of Zilina, 2010)
This paper examines the area of borrowings, the definition of borrowing as a process, the broader debate on the conditions of borrowing, reasons for borrowing describing both linguistic and extralinguistic aspects, the stratification of borrowings with its subclasses and consequent terminology. All of these issues are debated on the basis of the work of Mary Serjeantson.